DESIGN AND DEVELOPMENT OF WAX SLOWING TOOLS ON WRITING BATIK FABRIC IN KUBE PUTRI KAWUNG - Zulfiar Rifan Fadela Dardiri (Sekolah Vokasi Universitas Diponegoro, 2022)
This study examines the design of the written batik hook in the KUBe Putri Kawung industry, which is located in Jarum Village, Bayat District, Klaten Regency, Central Java. This research focuses on the process of making written batik cloth and designing the batik cloth sizing tool. This research is based on the process of batik cloth sag in KUBe Putri Kawung which is less effective, has a lot of losses and takes a lot of time. This is what initiated the author to conduct this research. The design consists of a stove, boiler (cord) and calculation of heat transfer and consumption of firewood. The results of the design and calculations in this study obtained the design and specifications of the tool as well as the results of the calculation of heat transfer heat and consumption of firewood both daily and annually. The design and specifications of the furnace used has a size of 120 cm x 65 cm x 40 cm, which is made of basic building materials (sand, bricks and cement) which are permanent and capable of supporting 2 (two) boilers in one process. For the design and specifications of the kettle (cord) used, it is made of aluminum with a thickness of 3 cm and dimensions of 65 cm x 59 cm. For the calorific value of heat transfer that occurs is 18.20 J/s 0C, this result is greater than the previously used boiler made of used drums. Meanwhile, for the consumption of firewood, Putri Kawung KUBe in one felling process requires 10 logs with a volume of 0.0042 m3 each,so that the daily consumption is 0.042 m3 the annual consumption is 15.33 m3.